Wavelength Selective Photodetectors Integrated on a Single Composition‐Graded Semiconductor Nanowire. Issue 12 (3rd April 2018) - Hu, Xuelu; Liu, Huawei; Wang, Xiao; Zhang, Xuehong; Shan, Zhengping; Zheng, Weihao; Li, Honglai; Wang, Xiaoxia; Zhu, Xiaoli; Jiang, Ying; Zhang, Qinglin; Zhuang, Xiujuan; et al.
Abstract: Nanoscale wavelength sensitive photodetectors based on single nanostructures are of significance for realizing future integrated optoelectronic devices. In this work, wavelength selective photodetectors integrated on a single composition‐graded CdS x Se1− x nanowire are realized. The photodetectors show an obvious illumination wavelength related rectifying effect, which can be ascribed to the graded composition along the wire. By spatially resolved photocurrent imaging, it is shown that the photoresponse of composition‐graded photodetectors is not restricted to the near contact regions, but can be extended to the whole nanowire due to the active optical waveguide to the narrow bandgap contact. Furthermore, by fabricating multielectrodes at different sections of the composition‐graded nanowire, multi‐photodetectors with tunable wavelength response ranges and selective rectified ratio at different wavelengths are realized. This work provides a deeper understanding of the dynamics of photogenerated carriers in bandgap‐engineered nanostructure photodetectors and opens the path to promising potential applications in integrated photonic and optoelectronic devices. Abstract : Wavelength selective photodetectors are integrated on a single composition‐graded nanowire with high photoresponsivity and fast response speed. The specific electronic band structures and optical‐transport properties in the composition‐graded nanowires are responsible for wavelength selectivity.